Effects of nutrient enrichment on seagrass population dynamics: evidence and synthesis from the biomass–density relationships. (17th October 2013) - Cabaço, Susana; Apostolaki, Eugenia T.; García‐Marín, Patricia; Gruber, Renee; Hernández, Ignacio; Martínez‐Crego, Begoña; Mascaró, Oriol; Pérez, Marta; Prathep, Anchana; Robinson, Cliff; Romero, Javier; Schmidt, Allison L.; et al.
Summary: The available data from experimental and descriptive studies on seagrass biomass and density responses to nutrient enrichment were analysed to assess the intraspecific mechanisms operating within seagrass populations and whether biomass–density relationships can provide relevant metrics for monitoring seagrasses. The response of shoot biomass and density to nutrient enrichment was dependent on the type of study; the short‐term positive response of biomass and density in experimental studies reveals context‐specific nutrient limitation of seagrasses. The long‐term negative response of descriptive studies probably results from ecosystem‐scale events related to nutrient enrichment such as increased turbidity, algal blooms, epiphyte loads and anoxia. Most seagrass species analysed lie in the nonthinning part of the theoretical biomass–density curves. A simultaneous increase in biomass and decrease in density, evidence of self‐thinning, were only observed in 4 of 28 studies. The analysis of both the static and the dynamic biomass–density relationships revealed that the slopes increase under nutrient enrichment. Surprisingly, the species‐specific slopes (log B‐log D) were higher than one, revealing that the B/D ratio, that is, the average shoot biomass, increases with density in all seagrass species analysed. Nutrient enrichment further enhanced this effect as biomass–density slopes increased to even higher values. The main drivers behind the increasing biomass–density slopes under nutrient enrichment were the increase in shoot biomass at densities above a species‐specific threshold and/or its decrease below that threshold. Synthesis . Contrasting short‐ and long‐term responses of both biomass and density of seagrasses to nutrient enrichment suggest that the former, positive ones result from nutrient limitation, whereas the later, negative ones are mediated by whole ecosystem responses. In general, shoot biomass of seagrasses increases with density, and nutrient enrichment enhances this effect. Experimental testing of facilitation processes related to clonal integration in seagrasses needs to be done to reveal whether they determine the low incidence of self‐thinning and the intriguing biomass–density relationships of seagrass species. The increasing slopes and decreasing intercepts of the species‐specific dynamic biomass–density relationships of seagrasses and the decreasing coefficients of variation of both biomass and density constitute relevant, easy‐to‐collect metrics that may be used in environmental monitoring. Abstract : Contrasting short‐ and long‐term responses of both biomass and density of seagrasses to nutrient enrichment suggest that the former, positive ones result from nutrient limitation whereas the later, negative ones are mediated by whole ecosystem responses. In general, shoot biomass of seagrasses increase with density and nutrient enrichment enhances this effect. Experimental testing of facilitation processes related to clonal integration in seagrasses needs to be done to reveal if they determine the low incidence of self‐thinning and the intriguing biomass‐density relationships of seagrass species. The increasing slopes and decreasing intercepts of the species‐specific dynamic biomass‐density relationships of seagrasses and the decreasing coefficients of variation of both biomass and density constitute relevant, easy‐to‐collect metrics that may be used in environmental monitoring.